Identification of the novel SDR42E1 gene that affects steroid biosynthesis associated with the oculocutaneous genital syndrome. (August 2021) - Bouhouche, Ahmed; Albaroudi, Nada; El Alaoui, My Abdelaziz; Askander, Omar; Habbadi, Zineb; El Hassani, Amine; Iraqi, Hinde; El Fahime, Elmostafa; Belmekki, Mohammed
Abstract: Hereditary connective tissue diseases form a heterogeneous group of disorders that affect collagen and extracellular matrix components. The cornea and the skin are among the major forms of connective tissues, and syndromes affecting both organs are often due to mutations in single genes. Brittle cornea syndrome is one of the pathologies that illustrates this association well. Furthermore, sex hormones are known to play a role in the maintenance of the structure and the integrity of the connective tissue including the skin and cornea, and may be involved in pathogenesis of oculocutaneous diseases. Herein, a double consanguineous family of Moroccan origin with two affected siblings, with suspected brittle cornea syndrome, was recruited. Ophthalmic examinations and genetic testing were performed in all the nuclear family individuals. Clinical examinations showed that the two affected boys presented with thinning of the cornea, blue sclera, keratoconus, hyperelasticity of the skin, joint hypermobility, muscle weakness, hearing loss and dental abnormalities that are compatible with the diagnosis of BCS disease. They showed however additional clinical signs including micropenis, hypospadias and cryptorchidism, suggesting abnormalities in endocrine pathways. Using a duo exome sequencing analysis performed in the mother and the propositus, we identified the novel homozygous missense mutation c.461G > A (p.Arg154Gln) in the short-chain dehydrogenase/reductase family 42E member 1 (SDR42E1) gene. This novel mutation, which co-segregated with the disease in the family, was predicted to be pathogenic by bioinformatics tools. SDR42E1 stability analysis using DynaMut web-server showed that the p.Arg154Gln mutations has a destabilizing effect with a ΔΔG value of −1.039 kcal/mol. As this novel gene belongs to the large family of short-chain dehydrogenases/reductases (SDR) thought to be involved in steroid biosynthesis, endocrinological investigations subsequently revealed that the two patients also had low levels of cholesterol. Karyotyping revealed a normal 46, XY karyotype for the two boys, excluding other causes of disorders of sex development due to chromosomal rearrangements. In conclusion, our study reveals that mutation in the novel SDR42E1 gene alters the steroid hormone synthesis and associated with a new syndrome we named oculocutaneous genital syndrome. In addition, this study highlights the role of SDR42E1 in the regulation of cholesterol metabolism in the maintenance of connective tissue and sexual maturation in humans. Highlights: The WES is a powerful method to discover new genes responsible for inherited diseases. Mutation in the SDR42E1 gene affects the steroid hormone synthesis. Mutation in the SDR42E1 gene associated with a new oculocutaneous genital syndrome. The SDR42E1 plays a role in the regulation of cholesterol metabolism. The SDR42E1 plays a role in the maintenance of connective tissue.